Is the Short Rate Drift Actually Nonlinear? - Chapman, David A.; Pearson, Neil D. (Journal of Finance, 2000)
Aït‐Sahalia (1996) and Stanton (1997) use nonparametric estimators applied to short‐term interest rate data to conclude that the drift function contains important nonlinearities. We study the finite‐sample properties of their estimators by applying them to simulated sample paths of a square‐root diffusion. Although the drift function is linear, both estimators suggest nonlinearities of the type and magnitude reported in Aït‐Sahalia (1996) and Stanton (1997) . Combined with the results of a weighted least squares estimator, this evidence implies that nonlinearity of the short rate drift is not a robust stylized fact.